2013
DOI: 10.1021/la401176j
|View full text |Cite
|
Sign up to set email alerts
|

Strict In-Plane Alignment Control of Block-Copolymer-Templated Mesostructured Silica Films Using an Alignment-Controlling Agent

Abstract: An alkoxysilane with an alkyl chain is introduced as an alignment-controlling agent of a block-copolymer-templated mesostructured silica film. Use of the alkylalkoxysilane achieves the alignment of the mesochannels of a triblock-copolymer-templated film by an intermolecular interaction with a rubbing-treated polyimide film. Co-use of an alkoxysilane with a hydroxymethyl group as a hydrophobicity reducing agent improves the alignment close to that of the film prepared using an alkyl surfactant. This concept wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Usually, silica membranes that are prepared by calcination of silica sol-coated films are rather hydrophobic. The results clearly indicate that the post-treatment of HMTES-containing membranes with water offers a new convenient method to increase the hydrophilicity of the silica membranes.Although homo-and copolymerization of HMTES giving the polymer gels have been studied, their utilities as separation membranes and post-hydrolysis of the polymers tuning the hydrophilicity have not yet been reported to our knowledge [27][28][29][30]. Chart 1.Chemical structures of alkoxysilanes investigated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, silica membranes that are prepared by calcination of silica sol-coated films are rather hydrophobic. The results clearly indicate that the post-treatment of HMTES-containing membranes with water offers a new convenient method to increase the hydrophilicity of the silica membranes.Although homo-and copolymerization of HMTES giving the polymer gels have been studied, their utilities as separation membranes and post-hydrolysis of the polymers tuning the hydrophilicity have not yet been reported to our knowledge [27][28][29][30]. Chart 1.Chemical structures of alkoxysilanes investigated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…35 However, in most of these methods, the evaporation-induced self-assembly process was not considered significantly. The process plays an important role in determining the structure of mesostructured silica films, and the relevant fundamental research of the process should contribute to the advancement of the methods described above.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, a variety of techniques have been reported for the production of two-dimensional hexagonal mesoporous thin films with the desired mesopores. The methods can be categorized into four groups: (i) synthesis under external forces such as electric field, magnetic field, and air flow; (ii) surface treatment by photoinduced anisotropic polymer film and cubic mesoporous film and rubbing treatment; (iii) geometrical surface modification such as lithographically designed confined space; , and (iv) addition of alignment-controlling agents . However, in most of these methods, the evaporation-induced self-assembly process was not considered significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the case of poly(ethylene oxide) (PEO)/poly(propylene oxide) (PPO) copolymers, it was shown that an overall BCP concentration of 60 to 70 wt% was necessary to obtain a hexagonal structure. 140 Variation of concentration or addition of NPs or nano-materials, 141,142 such as carbon nanotubes, 140 leads to a change in crystalline structure, typically resulting in spherical shapes at low concentrations and lamellar structures at high concentration, while increased temperature was shown to re-organize micelles from spherical to rod-like structure. 143 The incorporation of metal NPs may be performed either through direct mixing of metal NPs with a single BCP or a mixture of BCPs, 38 or by the in situ growth of metal NPs within the BCP macro-structure from metal precursors.…”
Section: Solid Phase Formingmentioning
confidence: 99%